Laboratory detection and rotational spectroscopy of trans-HNSO: implications for astronomical observations - Lattanzi, Valerio; Sanz-Novo, Miguel; Rivilla, Víctor M.; Jiménez-Serra, Izaskun; Caselli, Paola (Frontiers in Chemistry, 2025)
Sulfur-bearing molecules are central to interstellar chemistry, yet their observed abundances in the gas phase remain far below cosmic expectations in dense interstellar regions. Mixed N–S–O species such as thionylimide (HNSO) are particularly relevant, as they incorporate three key biogenic elements. The cis conformer of HNSO has recently been detected in the Galactic Center cloud G+0.693–0.027, but no high-resolution data for the higher energy conformer (trans-HNSO) had been available until now. We report the first laboratory detection and rotational spectroscopic characterization of trans-HNSO. Spectra were recorded with the Center for Astrochemical Studies Absorption Cell (CASAC) free-space spectrometer employing a hollow-cathode discharge source, yielding 104 assigned transitions between 200 and 530 GHz. A Watson S-reduced Hamiltonian fit reproduced the data with an rms of 40 kHz, providing accurate rotational and centrifugal distortion constants in excellent agreement with CCSD(T) predictions. Although trans-HNSO lies only a few kcal/mol above the cis form, it has larger dipole components, making its lines particularly intense (more than 5 times brighter, assuming equal abundances) and a very promising candidate for future astronomical detection. The new measurements enable reliable frequency predictions for astronomical searches and will be added to public databases. Combined with recent evidence for tunneling-driven trans-to-cis isomerization at cryogenic temperatures, these results open the way to test directly whether quantum tunneling governs the interstellar distribution of HNSO isomers.